Tackling Noncommunicable Diseases in Bangladesh : Now is the Time - El-Saharty, Sameh (Washington, DC: World Bank, 2013)
This report is organized in such a way that the key policy options and strategic priorities are based on the country context, including the burden of non-communicable diseases (NCDs) and associated risk factors and the existing capacity of the health system. Chapter one describes the country and regional contexts and the evidence of the demographic and epidemiological transitions in Bangladesh; chapter two outlines the disease burden of major NCDs, including the equity and economic impact and the common risk factors; chapter three provides an assessment of the health system and its capacity to prevent and control major NCDs; chapter four summarizes ongoing NCD interventions and activities in Bangladesh and highlights the remaining gaps and challenges; and chapter five presents key policy options and strategic priorities to prevent and control NCDs.